Optimal irrigation strategies for cowpea green bean production - Ramos, Herbert Moraes Moreira; Bastos, Edson Alves; Andrade Júnior, Aderson Soares de; Marouelli, Waldir Aparecido (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this work was to determine optimal strategies of irrigation for cowpea (Vigna unguiculata) for the production of green bean, with water as the limiting yield factor and different values for the price of the product. The experiment was carried out at Embrapa Meio‑Norte, in Teresina, PI, Brazil, from September to November 2009. Five irrigation depths, established based on fractions of reference evapotranspiration (25, 50, 75, 100, and 125% of ETo), and the BRS Guariba and BRS Paraguaçu cowpea cultivars were evaluated. Irrigation was done with a conventional fixed sprinkling system. The experimental design was a randomized complete block with four replicates, in a split‑plot arrangement (cultivars). The irrigation depths from 290 to 325 mm (108 to 130% of ETo) (BRS Paraguaçu) and from 325 to 363 mm (130 to 153% of ETo) (BRS Guariba) maximize the liquid income, considering the price range of the product from US 0.75 to 2.00 kg-1, for the cultivar BRS Paraguaçu, and from US 0.50 to 2.00 kg-1, for BRS Guariba. The cultivar BRS Guariba shows better economic performance than BRS Paraguaçu.